THE DIFFERENT FACES OF CHRIST IN ASIA - Parappally, Jacob (Asian Horizons, 2017)
All those Christians who live in the vast continent Asia, having an existential experience of the different cultures, sharing the world-view of the people, encountering everyday people of different religious traditions and listening to the cries of people who struggle to lead a life worthy of human beings raise the question about the meaning of Jesus Christ in the lives of the people of Asia. How does Jesus appear to the people of Asia? He has different faces in Asia. His face among the Chinese and other East Asian cultures is different from that of the Indian Subcontinent. Jesus is seen as the liberator of the oppressed Minjung people of Korea, the Dalits in India and other poor and oppressed people of Philippines and other countries as well as the liberator of Asian women. Since Jesus is identified with every humanizing culture of the Asian people and their struggle for full humanity they would find his face that is liberating, reassuring and meaningful to them in their own cultures and in their struggles, sometimes hidden, sometimes revealed but always challenging and liberating.